The behavior of Fe and S isotopes in porphyry copper systems: Constraints from the Tongshankou Cu-Mo deposit, Eastern China. (1st February 2020) - He, Zhiwei; Zhang, Xingchao; Deng, Xiaodong; Hu, Hao; Li, Yang; Yu, Huimin; Archer, Corey; Li, Jianwei; Huang, Fang
Abstract: Iron isotopes have been widely applied to trace mineralization processes of magmatic-hydrothermal ore systems, yet the application of Fe isotopes in porphyry Cu deposits (PCDs) is still restricted by the lack of understanding of its behaviors during hydrothermal alteration and ore formation processes. In this study, Fe isotope systematics in whole-rocks and Fe-bearing minerals coupled with S isotope compositions of Fe-sulfides are investigated for the early Cretaceous Tongshankou porphyry Cu-Mo deposit from Eastern China. The results show that altered ore-hosting granodiorite porphyries display a small δ 56 Fe variation (0.04‰ to 0.17‰) with an average of 0.10 ± 0.08‰ (2SD, n = 10), indistinguishable from the values for global igneous rocks. The δ 56 Fe of magnetite (0.22‰) and biotite (-0.08‰ to 0.12‰) from the altered porphyries are also within the δ 56 Fe ranges of those from global igneous rocks. These results indicate that hydrothermal fluids have negligible effect on Fe isotope compositions of the porphyry host rocks, likely due to the insignificant contributions of fluid-derived iron relative to the total Fe budget of the host rocks. The Fe-sulfides in the porphyry system record geochemical and iron isotopic characteristics of the ore-forming fluids. Specifically, chalcopyrites show large Fe isotope variations with δ 56 Fe ranging from −0.60‰ to 0.61‰. The calculated Fe isotope compositions of ore-forming fluids based on the chalcopyrite δ 56 Fe are thus not uniform and fall in the range from −0.69 ± 0.18‰ to 0.52 ± 0.18‰ (2SD). On the other hand, pyrites exhibit a δ 56 Fe variation between −0.48‰ and 0.40‰ and show distinct Fe isotopic characteristics for disseminated and vein-type pyrite. The δ 56 Fe for disseminated pyrites are consistently higher than whole-rock values, ranging from 0.14‰ to 0.40‰, likely reflecting equilibrium Fe isotopic exchange between pyrite and dissolved Fe in fluid. By contrast, δ 56 Fe for pyrites in veins are highly variable (−0.48‰ to 0.34‰) and show an inverse correlation with the chalcopyrite δ 56 Fe. These observations, in concert with S isotope data, have been interpreted to reflect pyrite formation through the FeS pathway, whereas the wide range in δ 56 Fe for pyrite may record isotopic change from initial FeS-fluid equilibrium towards pyrite-fluid equilibrium due to different extent of reaction upon precipitation. Additionally, when compared to sulfides formed by non-magmatic, low-temperature processes, the sulfides in our study exhibit a relatively narrow range of δ 56 Fe and δ 34 S, implying a high-temperature magmatic origin for both elements. Overall, our study demonstrates that the coupling of Fe and S isotopes could be a useful tool for tracking the processes of sulfide mineralization in porphyry-related deposits.